2012
DOI: 10.1590/s1516-35982012000300002
|View full text |Cite
|
Sign up to set email alerts
|

Agroindustrial byproducts in diets for Nile tilapia juveniles

Abstract: -This study was conducted to evaluate performance and body composition of tilapia (Oreochromis niloticus) fed diets containing byproducts aerial parts of cassava meal (Manihot esculenta), mesquite pod meal (Prosopis juliflora), cocoa meal (Theobroma cacao) and palm kernel cake (Elaeis guineensis) and to analyze the economic viability of the feed. A total of 1,350 juvenile males (100 g) were distributed in 15 cages (1 m 3 ) in completely randomized design with five treatments (basal diet and four test diets) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
4
0
2
Order By: Relevance
“…A common difficulty, observed when new additives or alternative food sources are used in fish diets, is acceptability, which is related to palatability (AZEVEDO; TONINI; BRAGA, 2013;CARVALHO et al, 2012;RODRIGUEZ;CARMONA, 1996;SENA et al, 2012). The similarity in values for total feed consumption suggests that including the additives under evaluation did not alter the palatability of the feed.…”
Section: Resultsmentioning
confidence: 99%
“…A common difficulty, observed when new additives or alternative food sources are used in fish diets, is acceptability, which is related to palatability (AZEVEDO; TONINI; BRAGA, 2013;CARVALHO et al, 2012;RODRIGUEZ;CARMONA, 1996;SENA et al, 2012). The similarity in values for total feed consumption suggests that including the additives under evaluation did not alter the palatability of the feed.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, there was no influence of pre-, pro-and synbiotic supplementation on the DFI. A common difficulty observed when new supplements or alternative food sources are used in fish feed is the acceptability, which is related to palatability (Carvalho, Azevedo, Ramos, & Braga, 2012). The similarity in feed intake values in this study suggests that the supplementation of the evaluated supplements did not alter the palatability of feed.…”
Section: Resultsmentioning
confidence: 52%
“…Therefore dietary CBM supplementation resulted in an improvement of economic efficiency. In contrast, Carvalho, et al [ 24 ] reported an increase in the relative feed costs in diets supplemented with the cocoa meal compared to the control diet that can be attributed to the cost difference per kg of the diet so the economic analysis depends on the animal performance indexes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the flavonoids in cocoa have been shown to have promising anti-cancer properties in test-tube and animal studies [ 23 ]. No mortalities were reported from using cocoa meal in Nile tilapia diets up to 150 g kg −1 [ 24 ].…”
Section: Introductionmentioning
confidence: 99%